Pendampingan Guru PJOK SD Dalam Desain Pembelajaran Penjas Melalui Tinju Tradisional “Sagi” Di Gugus Golewa Kabupaten Ngada - Wani, Bernabas; Bate, Nikodemus (PELITA NUSA TENGGARA, 2025)
Community service activities aim to enhance the capacity of elementary school physical education (PJOK) teachers in designing innovative, culturally rooted learning through the traditional martial art of “Sagi.” The main issue faced by the partner group elementary school teachers in the Golewa Cluster, Ngada Regency is the lack of knowledge and skills in teaching traditional sports, as well as the absence of structured teaching materials or instructional modules. To address this issue, the service team carried out a series of mentoring activities including: needs assessment, training in instructional design for basic “Sagi” boxing, and classroom-based teaching simulations. This approach is expected to improve teachers’ pedagogical competence and strengthen students’ character education by integrating local cultural values such as discipline, courage, and cooperation. Evaluation results showed an increase in teachers’ understanding of how to design and implement PJOK learning using “Sagi” boxing in a more contextual and engaging manner. The activity demonstrated that practice-based mentoring supported by digital media can effectively address the challenges of PJOK instruction in local contexts. It is also recommended that this program be replicated in other school clusters.